Strain-specific tropism and transcriptional responses of enterovirus D68 infection in human spinal cord organoids - Dábilla, Nathânia; Maya, Sarah; McNinch, Colton; Eddens, Taylor; Dolan, Patrick T.; Freeman, Megan Culler (Frontiers in Microbiology, 2025)
The mechanisms by which Enterovirus D68 (EV-D68) infection leads to acute flaccid myelitis (AFM), a severe neurological condition characterized by sudden muscle weakness and paralysis, remain poorly understood. To investigate the cellular tropism and infection dynamics of EV-D68, we profiled naive and EV-D68-infected human spinal cord organoids (hSCOs) derived from induced pluripotent stem cells (iPSCs) using single-cell RNA sequencing (scRNA-seq). Examining the cellular composition of healthy hSCOs, we found that hSCOs include diverse cell types, including neurons, astrocytes, oligodendrocyte progenitor cells (OPCs), and multipotent glial progenitor cells (mGPCs). Upon infection with 2 EV-D68 strains, US/IL/14-18952 (a B2 strain) and US/MA/18-23089 (a B3 strain), we observed distinct viral tropism and host transcriptional responses. Notably, US/IL/14-18952 showed a significant preference for neurons, while US/MA/18-23089 exhibited higher rates of infection in cycling astrocytes and OPCs. These findings provide novel insights into the host cell tropism of EV-D68 in the spinal cord, offering insight into the potential mechanisms underlying AFM pathogenesis. Understanding the dynamics of infection at single-cell resolution will inform future therapeutic strategies aimed at mitigating the neurological impact of enterovirus infections.